Functional gastrointestinal disorders frequency by Rome IV criteria - Claudia Alonso-Bermejo; Josefa Barrio; Beatriz Fernández; Elena García-Ochoa; Almudena Santos; Marta Herreros; Cristina Pérez (Elsevier, 2022)
Introduction: Functional gastrointestinal disorders (FGIDs) are a very common pediatric disease, with strong implications for children and their families. We aimed to determine their frequency in our environment (per Rome IV criteria) and to establish if there is seasonal variability in diagnosis. Methods: Descriptive, prospective study. For 12 months, children under 16 years of age with suspected FGIDs who had a first pediatric gastroenterology consultation were included and classified according to Rome IV criteria. Statistical analysis was done with SPSS v22. Results: 574 children received consultations, 67% were >4 years of age. FGIDs were suspected in 44.6% of the patients, 32.4% were diagnosed according to Rome IV criteria (16.4% <4 years, 40.3% >4 years). 51.1% were female, average age of 8.4 ± 4.2 years and mean of 7 months of symptoms until diagnosis (range 3-150). In patients <4 years, the most common disorders were functional constipation (48.4%), regurgitation (22.5%) and functional diarrhea (16.1%); in patients >4 years of age, functional abdominal pain (29%), functional dyspepsia (28.4%) and functional constipation (16.8%) were most frequent. We didn't discern seasonal variations in diagnosis in the global study population (p = 0.96) or by age group (<4 p = 0.51; >4 p = 0.57). Conclusions: FGIDs account for one third of our patients' consultations. While the Rome IV criteria are more inclusive than before, almost 30% of patients with suspected FGIDs don't meet said criteria. Although a seasonal difference regarding diagnosis was observed, it wasn't statistically significant either in the sample group as a whole or by age group. Resume: Introducción: Los trastornos funcionales gastrointestinales (TFGI) son una patología común en pediatría, con fuertes implicaciones para el niño y su familia. Nuestro objetivo es determinar su frecuencia en nuestro medio según criterios Roma IV y la posible variación estacional al diagnóstico. Material y métodos: Estudio descriptivo con recogida de información prospectiva. Durante un año se incluyeron menores de (<) 16 años que acudieron a primera consulta de Gastroenterología Pediátrica con sospecha de TFGI, a los que se clasificó según Roma IV. Análisis estadístico mediante SPSS v22. Resultados: Acudieron en total 574 niños, 67% mayores de (>) 4 años. Se sospechó TFGI en 44.6%, siendo diagnosticados según criterios Roma IV 32.4% (16.4% <4 años, 40.3% >4 años). 51.1% eran mujeres, edad media de 8.4 ± 4.2 años, y mediana de 7 meses de síntomas al diagnóstico (rango: 3-150). Por frecuencia, en <4 años destacan el estreñimiento (48.4%), la regurgitación (22.5%) y la diarrea funcional (16.1%); y en >4 años el dolor abdominal funcional no especificado (29%), la dispepsia funcional (28.4%) y el estreñimiento (16.8%). En el diagnóstico por trimestres no se objetivaron diferencias en el total (p = 0.96), ni por grupos de edad (<4 p = 0.51; >4 p = 0.57). Conclusión: Según Roma IV, los TFGI suponen un tercio de los pacientes de nuestra consulta. A pesar de ser más inclusivos que previamente, casi un 30% de los pacientes con sospecha no cumple criterios. Aunque existe cierta variación estacional en la frecuencia diagnóstica, no fue significativa ni en el total ni por grupos de edad.